Association between cognitive reserve and cognitive performance in people with HIV: a systematic review and meta-analysis. Issue 1 (2nd January 2020) - Kaur, Navaldeep; Dendukuri, Nandini; Fellows, Lesley K.; Brouillette, Marie-Josée; Mayo, Nancy
ABSTRACT: Cognitive reserve is a potential explanation for the disparity between brain pathology and its clinical manifestations. The main objective of this study was to estimate, based on published studies, the strength of the association between cognitive reserve and cognitive performance in individuals with HIV. A systematic literature search using Ovid MEDLINE, PsychINFO, and EMBASE was performed to identify studies published between 1990 and 2016 that quantified the association between cognitive reserve and cognitive performance in HIV. A random-effects meta-analysis was used to compute a summary estimate (Cohen's d ) with 95% confidence intervals (CI) and 95% prediction intervals (PI). The risk of bias and quality of reporting in the studies were indicated by the Appraisal tool for Cross-Sectional Studies (AXIS). Ten observational studies were deemed eligible. The pooled effect size was 0.9 (95% CI: 0.7–1.0; 95% PI: 0.4–1.4) with marked heterogeneity studies [Cochran's Q (df = 9) = 28.0, p = .0009; I 2 statistic = 67.4%]. Risk-of-bias appraisal showed that non-response bias was never addressed and the items associated with selection bias were only partially met. The association between cognitive reserve and cognitive performance suggests that building reserve through non-pharmacological interventions could be a potentially effective way of combating cognitive impairment in people with HIV.